Changes and imbalance of Th1 and Th2 immune response in pediatric patients with seasonal allergic conjunctivitis - Palabiyik-Yucelik Saziye Sezin; Cinici Emine; Sipahi Hande; Baydar Terken (Pteridines)
Helper T (Th) 1 inflammatory cytokines, like interferon gamma, play a role in the active inflammatory phase of ocular allergic diseases in addition to Th2-type cytokines, which are actively involved in the pathogenesis of allergies. Allergic conjunctivitis is one of the most common syndromes in ocular disorders, with a prevalence of 5–22% in the general population. The goal of this study was to evaluate the serum neopterin and immunoglobulin E (IgE) levels, as well as the kynurenine (Kyn)/tryptophan (Trp) ratio as an indicator of indoleamine 2,3-dioxygenase activation, in 44 pediatric patients with seasonal AC (SAC) in comparison with values from 33 healthy children. We also assessed the correlations between these biomarkers and symptom and sign scores. Serum neopterin levels were significantly higher in patients with SAC than in healthy controls (p = 0.018) and were significantly correlated with all parameters except the sign score among the patients. Serum IgE was also higher (p < 0.001) and Trp levels were significantly lower (p = 0.017) among patients, while Kyn levels and the Kyn/Trp ratio did not differ between the groups. In conclusion, our study indicated that both Th1 and Th2 responses are active in SAC, confirming the complex involvement of both cytokines in this pathology.